Antisense Oligonucleotides and Magnetic Nanoparticles for Targeted Diagnostic and Cancer Treatment. - Ruiz-Gómez, Miguel José; López-Díaz, Beatriz; Mercado-Sáenz, Silvia; Sendra-Portero, Francisco (MedCrave, 2017)
The resistance of tumors to therapeutic intervention is a major problem in the efficacy of treatments. A recent strategy to overcome this problem proposes the association of antitumor drugs with colloidal nanoparticles. Here a hypothesis is suggested concerning the potential use of antisense Oligo Deoxy Nucleotide (ODN) labeled with iron nanoparticles for tumor antisense gene detection with magnetic resonance gene imaging and cancer treatment.
Keywords: Nanopartículas; antisense therapy; magnetic field; drug delivery; nanoplatform; nanoparticles; nanobiotechnology